Exhaled nitric oxide in chronically ventilated preterm infants. Issue 1 (1st January 2004) - Williams, O; Bhat, R Y; Cheeseman, P; Rafferty, G F; Hannam, S; Greenough, A
Abstract : Exhaled nitric oxide (eNO) levels were measured in eight ventilated infants, mean gestational age 25.8 (SD 1.7) weeks and postnatal age 55 (SD 39) days, before and after three days of dexamethasone treatment. The eNO levels fell from a mean of 6.5 (SD 3.4) to 4.2 (SD 2.6) parts per billion (p = 0.031) and the mean supplementary oxygen levels from 62% to 45% (p = 0.0078).